Application of Proportional Importance Index in Industrial Hazards Identification and Assessment of Safety Measures in the Chemical Industry - G. C. Afube; Ify L. Nwaogazie; J. N. Ugbebor (New Ideas Concerning Science and Technology Vol. 6, 2021)
Hazards identification and creation of a safe working environment is a major challenge faced by management of many industries today. Hazard assessment is thus carried out in workplaces to identify dangerous events and conditions that may lead to accidents in the industries. Gap analysis on hazard identification alongside safety management in the industries was carried out in order to showcase the level of incompleteness in recent studied on the subject and the need to close the gaps in future studies. This study, which was carried out in both a petrochemical and an oil refining companies in Nigeria, identified industrial hazards and assessed safety measures in the Chemical Industry (CHI) of Nigeria. A well-structured questionnaire instrument was used for data collection. The study was carried out amongst technical staff and management staff of the chemical industry whose day-to-day duty is such that they are exposed to one form of hazard or the other in the industry. The questionnaire was administered to 96 technical staff and management staff in the CHI out of which 84 (88%) were completed and returned. The study focused on types of hazards, hazards and risk awareness, implementation of control measures and effectiveness of safety hazards and risk management programmes in the chemical industry of Nigeria. Modified Proportional Importance Index (PII) and a four-point Likert scale were adopted in data analysis. Results revealed that loud noise (PII = 3.2; respondents = 92%), working at heights (with PII = 3.1; respondents = 89%) machines and equipment vibration (PII = 3.0; respondents = 87%), high voltage areas (PII = 2.9; respondents = 84%) and chemical spills (PII = 2.5; respondents = 55%) are the highest ranking hazards in the chemical industry. A high level of safety hazard awareness was found among workers in the industry (p < 0.05, 95%Cl.; PII = 3.1 - 3.5). The outcome of the intervention showed that Chemical Industry Number 1 (CHI-1) improved from 87.90% to 98.09%, Chemical Industry Number 2 (CHI-2) improved from 81.53% to 95.54% on worker’s knowledge on the identification and assessment of hazards and risk in the chemical industries. These hazards pose threats to the safety of workers and should be effectively controlled to reduce associated risks to as Low as Reasonably and Practically Achievable (ALARPA).